2020
DOI: 10.1002/brb3.1694
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐dependent alterations of dopamine receptor and glucose transporter density in rat hypothalamus under long‐term clozapine and haloperidol medication

Abstract: Objective Sex‐dependent disturbances of peripheral glucose metabolism are known complications of antipsychotic drug treatment. The influence of long‐term clozapine and haloperidol medication on hypothalamus, maintaining aspects of internal body homeostasis, has not yet been completely clarified. Methods After puberty, male and female Sprague Dawley rats were fed orally with ground pellets containing haloperidol (1 mg/kgBW/day) or clozapine (20 mg/kgBW/day) for 12 weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…It was established that yawning correlated with dopamine D3 receptor densities in various regions, including the globus pallidus, caudate nucleus, putamen, ventral pallidum, and hippocampus [ 90 ]. There is little information that exists on innate sex differences in dopamine D4 receptor expression and function; although, the antagonist clozapine, which has a high affinity for the D4 receptor, was found to increase hypothalamic D4 receptor expression to a greater extent in females compared to males [ 91 ].…”
Section: Sex Differences In D2-like Receptorsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was established that yawning correlated with dopamine D3 receptor densities in various regions, including the globus pallidus, caudate nucleus, putamen, ventral pallidum, and hippocampus [ 90 ]. There is little information that exists on innate sex differences in dopamine D4 receptor expression and function; although, the antagonist clozapine, which has a high affinity for the D4 receptor, was found to increase hypothalamic D4 receptor expression to a greater extent in females compared to males [ 91 ].…”
Section: Sex Differences In D2-like Receptorsmentioning
confidence: 99%
“…Little is known about sex-specific effects in dopamine function in schizophrenia, despite the presence of sex differences in onset and symptomatology [ 149 ]. Of these studies, the focus is less on the neuropathology of schizophrenia, but rather on sex differences in antipsychotic treatment responses [ 38 , 47 , 91 , 154 ]. A clinical study analyzed findings from four distinct PET imaging studies: three on schizophrenia and one on bipolar disorder [ 154 ].…”
Section: Sex Differences In Dopamine Receptors: Relevance To Neuropsychiatric Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal experiments have demonstrated sex effects on receptor uptake of radioactive ligands (8). One pre-clinical study has shown sex effects on the upregulation of D2 receptors after treatment with haloperidol or clozapine (9). In terms of effects in humans, Kaasinen et al (10) found that women had higher D2-like receptor binding potentials than men, especially in the left and right anterior cingulate cortex.…”
Section: Neurotransmitter Receptors and Sexmentioning
confidence: 99%